2022
DOI: 10.3390/healthcare10081453
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Study of Dental Structure in Dentinogenesis Imperfecta Type I with Scanning Electron Microscopy

Abstract: Background: Dentinogenesis imperfecta type I (DGI-I) is a hereditary alteration of dentin associated with osteogenesis imperfecta (OI). Aim: To describe and study the morphological characteristics of DGI-I with scanning electron microscopy (SEM). Material and methods: Twenty-five teeth from 17 individuals diagnosed with OI and 30 control samples were studied with SEM at the level of the enamel, dentin–enamel junction (DEJ) and four levels of the dentin, studying its relationship with clinical–radiographic alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…In previous studies, it has been hypothesized that the alteration of the dental microstructure is secondary to dysfunction of the odontoblasts due to intracellular accumulation of abnormal procollagen and collagen degradation products [11] or rapid obliteration of the dentinal tubules due to aberrant mineralization of the dentin [19]. In fact, the evidence seems to support the theory that the initial dentinal secretion would be normal if the formation of aberrant dentin begins later, since according to several authors [14,20,21], the outermost dentin has normal morphology, with a layer parallel to the dentin-enamel junction (DEJ) of dysplastic dentin continuing alternating dysplastic and tubular zones up to the pulpal tissue.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…In previous studies, it has been hypothesized that the alteration of the dental microstructure is secondary to dysfunction of the odontoblasts due to intracellular accumulation of abnormal procollagen and collagen degradation products [11] or rapid obliteration of the dentinal tubules due to aberrant mineralization of the dentin [19]. In fact, the evidence seems to support the theory that the initial dentinal secretion would be normal if the formation of aberrant dentin begins later, since according to several authors [14,20,21], the outermost dentin has normal morphology, with a layer parallel to the dentin-enamel junction (DEJ) of dysplastic dentin continuing alternating dysplastic and tubular zones up to the pulpal tissue.…”
Section: Introductionmentioning
confidence: 89%
“…In addition, it has been confirmed that the microstructural alteration occurs even in teeth that do not appear to show signs of clinical and/or radiographic signs of DGI-I [19,20,22]. The dentin alterations described in the literature are mainly a decrease in tubular diameter and density, with an abnormal pattern in the direction of the dentinal tubules and a dysmorphic appearance [11,14,19,20]. The severity of dentin alteration has also been related to the systemic alteration (OI), with dentin being more dysmorphic in the most severe OI phenotypes [20].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…A dentinogenesis imperfecta (DI) egy autoszomális dominánsan öröklődő betegség, amelyet a dentin súlyos hipomineralizációja és megváltozott szerkezete jellemez [1], izoláltan vagy az osteogenesis imperfecta (OI) néven ismert genetikai rendellenességgel társul [2,3]. A dentinogenesis imperfectát Shields és munkatársai [4] három kategóriába sorolták: az I-es típus az osteogenesis imperfectával társul, itt a tejfogak súlyosabban érintettek, mint a maradó fogak.…”
Section: Bevezetésunclassified